2021
DOI: 10.3390/nu13020563
|View full text |Cite
|
Sign up to set email alerts
|

Edible Microalgae and Their Bioactive Compounds in the Prevention and Treatment of Metabolic Alterations

Abstract: Marine and freshwater algae and their products are in growing demand worldwide because of their nutritional and functional properties. Microalgae (unicellular algae) will constitute one of the major foods of the future for nutritional and environmental reasons. They are sources of high-quality protein and bioactive molecules with potential application in the modern epidemics of obesity and diabetes. They may also contribute decisively to sustainability through carbon dioxide fixation and minimization of agricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 118 publications
0
67
0
Order By: Relevance
“…The former authors hypothesised that the reason for the decreased plasma TAG concentration of laying hens was the inhibition of hepatic fatty acid synthesis and triacylglycerol production. Previous studies have shown that the nutritional composition of C. vulgaris may contribute to their effects on mitigating metabolic alterations through different mechanisms [ 36 , 37 ]. Several algae-derived bioactive compounds, like lipids, antioxidants, pigments, vitamins and polysaccharides are known to have beneficial effects on human and animal health [ 38 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The former authors hypothesised that the reason for the decreased plasma TAG concentration of laying hens was the inhibition of hepatic fatty acid synthesis and triacylglycerol production. Previous studies have shown that the nutritional composition of C. vulgaris may contribute to their effects on mitigating metabolic alterations through different mechanisms [ 36 , 37 ]. Several algae-derived bioactive compounds, like lipids, antioxidants, pigments, vitamins and polysaccharides are known to have beneficial effects on human and animal health [ 38 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it is to recall that Spirulina species belong to cyanobacteria and contain both chlorophyll and phycocyanins, the respective green and blue pigments involved in photosynthesis, making Spirulina species to be commonly defined as a blue-green alga. Phycocyanins exhibit special spectral properties in term of high absorbance and fluorescence yields, accounting for their photoprotection role in cyanobacteria and for more general strong antioxidant properties, which have stimulated the use of phycocyanins in nutriceutics and pharmacology, besides the use in food and pharmaceutics as a mere dye [15,50,51,[54][55][56][57][58][59]. The absorption and fluorescence properties of purified phycocyanin and allophycocyanin have been also analyzed by time-resolved techniques to investigate ultrafast kinetic components of excitation energy transfer in phycobilisome, with the aim to improve the collection of solar energy for photovoltaic applications [15].…”
Section: Chlorophyll and Algaementioning
confidence: 99%
“…The main fluorophores described in this section are summarized in Table 2. [10,22,23] Abiotic stress in higher plants [39] Phycocyanin Allo-phycocyanin 550-670 nm 650-700 nm Light harvesting, efficient energy conversion, photoprotection in cyanobacteria [58] Food and pharmaceutic additives [15,50,51,[54][55][56][57][58][59] Models to improve photovoltaic applications [15] * Other optical parameters besides absorption/fluorescence may have been used in some applications; excitation/emission ranges may vary depending on measurement conditions.…”
Section: Chlorophyll and Algaementioning
confidence: 99%
See 1 more Smart Citation
“…Chlorella contains dietary fibre such as β-glucan that is metabolised to short-chain fatty acids (SCFAs) such as propionate and butyrate, which are known to have beneficial effects on host health, by the gut microbiota (15). However, a simple comparison showed no significant difference in the faecal abundances of propionate and butyrate before and after Chlorella intake in this study (Figures 4A,C).…”
Section: Correlation Analysis Revealed That the Effect Of Chlorella Intake Depends On The Individual Intestinal Environmentmentioning
confidence: 59%